ALTAS HABILIDADES/ SUPERDOTAÇÃO NA PERSPECTIVA SOCIOCULTURAL: DILEMAS, DESAFIOS E DIREÇÕES FUTURAS PARA FORMAÇÃO DE PROFESSORES - DORINI, ELIESI BETTIN CHAVES (2019)
This research aimed to analyze if the mediation of a continuous teacher training course contributes to the elaboration of knowledge, which allows teachers to understand and identify the high skills / giftedness and propose pedagogical referrals. Twenty-seven teachers who work in Elementary School II and in the Multifunctional Resource Rooms, participated in this research in two educational institutions of the state education network in the city of Mangueirinha-PR. The research is qualitative approach, characterized as action research and for data collection were used as instruments: the interview, the participatory intervention and the questionnaire. The semi-structured interview comprised the first stage of the research, containing questions with open questions, divided into two categories: Teacher Education: academic training, time and professional performance of teachers; and High Skills / Giftedness: Initial and Continuing Education; knowledge, concepts, characteristics, classroom recognition, identification process and professional performance. For the accomplishment of the participatory intervention it was elaborated Training Course: “High Skills / giftedness: But does that exist? ”, Structured in face-to-face meetings addressing various conceptual aspects and the use of psychopedagogical tools to identify students with high skills / giftedness in the school context. After the course, a questionnaire with open questions was applied, in order to know the knowledge elaborated and built on the high skills / giftedness. Vygotsky's historical-cultural theory is the theoretical basis of the data analysis and interpretation approach, since it is a school-based research and the foundation of the high-skills / gifted sociocultural model, which considers the sociocultural aspects according to the function of the socio-cultural, temporal and historical period in which the triad is contextualized: family, school and colleagues. The results of this research generally pointed to a lack of knowledge about high skills / giftedness in the school context, although it is a specificity of Special Education, in an inclusive perspective based on years in the school context. The data also showed the urgency of covering high skills / giftedness in initial teacher education courses, as well as the offer of continuing education in all spheres, levels and modalities of education. They have also shown that teachers argue that these students need to be identified and need specialized educational care. Thus, it is expected that this work will contribute to the advancement of the discussion about high skills / giftedness, offering theoretical and methodological support for the teaching practice.